PWE-086 Prevalence of dual pathology in routine liver biopsies. (22nd June 2015) - Paterson, AL; Brais, R; Davies, SE
Abstract : Introduction: The indications for liver biopsy are changing with their role in diagnosis becoming less, and alternative assessments being increasingly used for staging purposes. There is an emerging impression that more biopsies are being taken for an element of clinical uncertainty, particularly when multiple risk factors are present. This study aimed to determine (a) the number of medical liver biopsies in which a primary and secondary diagnosis were identified; (b) whether this had changed over time; and (c) the most prevalent co-existing pathologies. Method: All liver biopsies reported at our centre, a tertiary referral liver unit and transplant centre, in 2003 and 2013 were identified from the electronic record. Biopsies from liver transplant grafts and of focal lesions were excluded. The histopathology report for each case was reviewed, the number of different pathologies present recorded and then correlated with the clinical information provided. Results: In total, 1421 liver biopsies met the inclusion criteria. In 2013, 189/941 (21%) had more than one pathology present, a proportion comparable to 2003, 85/480 (18%), p = 0.32. Three co-existing disease processes were present in 1% (13/1421) of cases. Based on the clinical details provided at the time of biopsy, in 213 (78%) cases overall, the additional pathology (s) was not suspected. In 2003, the most prevalent reported pathology as a primary or dual diagnosis was chronic viral hepatitis, present in 182/480 (38%) biopsies, with fatty liver disease second, 157/480 (33%). By 2013 this had reversed with significant fatty liver disease reported in 409/941 (43%) biopsies and chronic viral hepatitis in 260/941 (28%). In both years, in over a third of cases of fatty liver disease, and a quarter with chronic viral hepatitis, a dual pathology was present; most commonly these two aetiologies co-existing. When present, significant siderosis and alpha-1-antitrypsin accumulation were usually part of a dual diagnosis, 58/70 (83%) and 27/35 (77%) respectively. In 2013, compared to 2003, there was a 50% increase in the prevalence of cholangiopathies, siderosis and alpha-1-antitrypsin accumulation reported as part of a dual diagnosis; whilst autoimmune hepatitis was more likely to be a single diagnosis, 30% in 2013 compared to 57% in 2003. Conclusion: The proportion of dual diagnoses has not significantly changed in the decade studied and remains dominated by fatty liver disease. The disease combinations identified have however altered; this may reflect a better understanding of the pathological processes and clearer guidelines for diagnosis. Pathologists should be aware of the frequent occurrence of dual pathology as it has the potential to impact on clinical management and, based on the clinical details provided, a second diagnosis was not suggested in over three-quarters of cases identified in this study. Disclosure of interest: None Declared.